2011
DOI: 10.1094/pdis-05-10-0321
|View full text |Cite
|
Sign up to set email alerts
|

Polyphasic Characterization of Pigmented Strains of Xanthomonas Pathogenic to Cashew Trees

Abstract: Gama, M. A. S.. Mariano, R. L. R., Viana, F. M. P, Ferreira, M. A. S. V., and Souza, E. B. 2011. Polyphasic characterization of pigmented strains of Xanthomonas pathogenic to cashew trees. Plant Dis. 95:793-802.The export of cashew {Anacardium occidentale) nuts generates millions of dollars for the Brazilian economy annually. However, production may be limited by the occurrence of diseases that affect cashew trees, such as Xanthomonas spot and angular leaf spot, which are caused by pigmented strains of Xantlum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
2
3
0
1
Order By: Relevance
“…Anthracnose is by far the most important disease in the field, leading to significant yield losses. Our results are consistent with those of Freire et al [10] and Araújo [4]. Some studies revealed that fungi are responsible of gummosis [6].According to this author, up to now, despite the important damage induced by gummosis disease on cashew, no efficient measure is available to control it.…”
Section: Discussionsupporting
confidence: 92%
“…Anthracnose is by far the most important disease in the field, leading to significant yield losses. Our results are consistent with those of Freire et al [10] and Araújo [4]. Some studies revealed that fungi are responsible of gummosis [6].According to this author, up to now, despite the important damage induced by gummosis disease on cashew, no efficient measure is available to control it.…”
Section: Discussionsupporting
confidence: 92%
“…With exception of the hydrolysis of esculin, the Xcm 2103 has no enzymes that hydrolyze other tested substrates (Table 1). This biochemical profile was very similar to that from 68 strains of X. campestris mangiferaeindicae previously studied [16], as well as, to other 3 strains when tested for L-arginine, urease and indole hydrolysis [20]. According the results, the Xcm 2103 utilizes arabinose, sucrose and acetamide as carbon sources, promoting media acidification.…”
Section: Physiological and Biochemical Profilesupporting
confidence: 82%
“…Because X. ampelinus was previously classified as Xanthomonas ampelina, the repetitive sequence-based PCR method previously used for determining the genetic variation of Xanthomonas was applied in this study (Adhikari et al 2012;Gama et al 2011;Kawaguchi 2014;Mondal and Mani 2009;Rademaker et al 2005;Sahin et al 2003;). Box-PCR, ERIC-PCR, and Rep-PCR were performed using the primer sets BOX and BOXA1R; ERIC, ERIC1R, and ERIC2; and REP, REP1R-I, and REP2-I reported by Versalovic et al (1994), Hulton et al (1991), andMartin et al (1992), respectively.…”
mentioning
confidence: 99%